Relationship Between Gestational Age and Severity of Gingivitis - Dhandi Wijaya; Nur Adiba Hanum; Asih Handayani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Increased levels of the hormones estrogen and progesterone in the blood during pregnancy can cause gingivitis due to vascular changes that cause the gingiva to become more sensitive especially to toxins and other irritants, such as plaques and calculus, which causes the gingiva to become easily inflamed. Pregnancy can also aggravate gingivitis due to the excessive inflammatory response of the gingiva to dental plaque and hormonal changes that occur during pregnancy. This study aims to determine the differences in the degree of gingivitis in pregnant women in each trimester of gestational age. This study was a cross-sectional study conducted in April 2019 on 80 pregnant women with gingivitis who examined their pregnancies at the Puskesmas Merdeka Palembang during the fourth week of March 2019. The relationship between the degree of gingivitis in each trimester of pregnancy was analyzed using Fisher's exact test with 95% confidence interval. The results showed that gingivitis was found most frequently in third trimester pregnancy (47.5%) and mild gingivitis, mostly experienced by pregnant women in trimester II pregnancy (52.6%), while moderate and severe gingivitis was more experienced by trimester pregnant women III (50% and 81.8%). The statistical test results showed a significant relationship between the gestational age and severity of gingivitis (p 0.05). It can be concluded that increasing gestational age is related to the increasing severity of gingivitis.